Pengelolaan Kelas Dipandang dari Perspektif Psikologi - Irnes Jakli Sy (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2014)
This paper focuses on the problem of the management class. The views of the management ofclass had only understood as the ability piñata, control and regulate the class, so thatwell-organized classes and fun. Though not so. Management of the class was alsorelated to psychological aspects, administrative and paedagogis.In this paper the author tries to describe what are the components of classroom management, in addition tophysical aspects. So it can be understood that classroom management is a psychic and physical activityby teachers in designing the governance of the class in terms of psychology, administration and paedagogis.